Critical Thought from an Islamic Perspective - al-Najjar, Abd al-Majid (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2020)
This study treats an important aspect of education which Muslim educators have inadequately addressed, namely critical thought. Muslim educators, instead, have largely focused on spiritual and moral education; these having a predominant influence on the concept of education in the Islamic consciousness in general, and on religious leaders and educators in particular. The study thus holds that critical thought should be accorded appropriate importance, even more given the direct reflection it has on all facets of human conduct, both theoretical and practical. Attention to critical thought is necessitated, moreover, in light of the current reality of substantial deviations in understanding religion in particular, and in the aptitude of understanding in general; which is manifested in the lack of contribution to and development of scientific knowledge and the religious sciences. The study contends that neglect of critical thought has led to the emergence of extremism and terrorism, and has consequently brought considerable harm to the global Muslim community (Ummah).